Benefits and Costs of International Financial Integration : Theory and Facts - Agenor, Pierre-Richard (World Bank, Washington, DC, 2014)
The author provides a selective review of the recent analytical and empirical literature on the benefits and costs of international financial integration. He discusses the impact of financial openness on consumption, investment, and growth, and the impact of foreign bank entry on the domestic financial system. Consistent with some recent studies, the author argues that financial integration must be carefully prepared and managed to ensure that the benefits outweigh the short-run risks. Prudent macroeconomic management, adequate supervision and prudential regulation of the financial system, greater transparency, and improved capacity to manage risk in the private sector are important requirements for coping with potentially abrupt reversals in pro-cyclical, short-term capital flows. The author adopts a more skeptical view than some assessments in two areas, however. First, only foreign direct investment appears to provide dynamic gains and improved prospects for growth; the evidence on the benefits of other types of capital flows remains weak. Second, empirical research on the net benefits associated with foreign bank penetration is far from conclusive; in particular, the possibility that such penetration may lead to adverse changes in the allocation of credit among domestic firms cannot be dismissed on the basis of the existing evidence.